Penggunaan Mendeley sebagai Manajemen Referensi Karya Tulis - Syed Agung Afandi; Hijratul Aswad; Muslim Afandi; Rizki Erdayani; Saipul Alsukri (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Writing is one thing that cannot be separated from the campus world. Whether it's writing papers, research reports, thesis and writing research articles. One of the problems experienced by writers (students) in writing scientific articles is plagiarism and reference/bibliography management. One of the software that is often used in reference management is Mendeley. This service activity is carried out considering that many students still do not know the operation of this software in reference management. The training was attended by hundreds of students and carried out in a hybrid way (online and offline). The results of this activity are that participants can understand Mendeley's function in making scientific papers. Besides that, participants have also been able to install and use Mendeley to find relevant reference sources, make reference sources in a quote, create a bibliography, and manage reference sources.